2020
DOI: 10.9734/aprj/2020/v4i230082
|View full text |Cite
|
Sign up to set email alerts
|

Improving Maize Productivity under Rain-Fed Conditions through the Combined Use of Inorganic and Organic Fertilizer in Malawi

Abstract: Integrated soil fertility management was promoted on-farm during the 2018/2019 cropping season in Thyolo, Phalombe, Mulanje and Zomba districts of southern Malawi, in purposively selected extension planning areas (EPAs). Sixty farmers, fifteen from each district were involved. Trials were established in farmers’ fields with smallholder farms as replicates and extension EPAs as blocks. The following were the treatments; Maize + 92 kg N ha-1 + 46 kg of P ha-1; Maize + 3 tons of compost manure ha-1; and Maize + 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The fertility status of sites had no significance in terms of yield as indicated in the tables which could be as a result of cushioning factor of organic carbon which made the organic fertilisers to provide nutrients based on plant nutrient demand. This was equally reported by Phiri et al [24] where it was observed that combined application of organic and inorganic fertilisers gave the highest performance in maize grown in Malawi. Generally, OC in all sites was low indicating the need to restock and buildup OC as shown in Table 2.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The fertility status of sites had no significance in terms of yield as indicated in the tables which could be as a result of cushioning factor of organic carbon which made the organic fertilisers to provide nutrients based on plant nutrient demand. This was equally reported by Phiri et al [24] where it was observed that combined application of organic and inorganic fertilisers gave the highest performance in maize grown in Malawi. Generally, OC in all sites was low indicating the need to restock and buildup OC as shown in Table 2.…”
Section: Resultssupporting
confidence: 74%
“…However, no significant differences in maize grain yields were observed between treatments within a district because of buffer effect of manure. Studies have shown that crop nutrient demand and soil nutrient release is achieved through combined application of organic and inorganic fertilizer [24,26].…”
Section: Resultsmentioning
confidence: 99%